Patient Knowledge About Post-Laser Care at the Clinic: A Literature Review - Pramesti Adikara Ratri; Indah Indi Afifah; One Juniar Putri Pratama; Cinta Maharanisyah Lubis; Ines Deva Nareswari; Erlisa Dewi Mayangsari; Danu Mahardika (Global Writing Academica Researching and Publishing, 2026)
Laser therapy is one of the most widely used methods in dermatology and aesthetic medicine due to its ability to improve various skin conditions, such as hyperpigmentation, scarring, premature aging, and chronic wounds. The mechanism of laser action, based on the principle of selective photo thermolysis, allows light energy to be selectively absorbed by target tissues without damaging the surrounding areas, making this therapy effective and relatively safe. In addition to providing therapeutic effects such as accelerating wound healing, reducing inflammation, and stimulating collagen production, laser therapy also induces biological responses in the skin that require special attention during the post-treatment phase. Therefore, Post-Laser Care becomes an essential and inseparable part of the overall success of the therapy. This study aims to examine patients’ knowledge regarding Post-Laser Care through a literature review method using a narrative approach. Data were obtained from various relevant scientific articles that met the inclusion criteria, such as a minimum publication year of 2016, topic relevance, and full-text accessibility. The analysis process was conducted through identification, screening, and synthesis of research findings. The results indicate that post-laser care plays a crucial role in accelerating the healing process, maintaining skin hydration, preventing complications such as infection and hyperpigmentation, and sustaining long-term therapeutic outcomes. Furthermore, patients’ level of knowledge has been shown to have a significant relationship with attitudes and care practices (knowledge, attitude, practice), where better understanding promotes adherence to medical instructions. Therefore, comprehensive, structured, and continuous education from healthcare professionals is highly necessary to improve patients’ knowledge and behavior, thereby optimizing laser therapy outcomes and minimizing the risk of complications.